Tensile Strength and Fracture Behavior of Single Abaca Fiber. Issue 14 (28th October 2022) - Sabri, Sabri; Fuadi, Zahrul; Kurniawan, Rudi; Rizal, Samsul; Homma, Hiroomi; Kosukegawa, Hiroyuki; Takagi, Toshiyuki; Miki, Hiroyuki
ABSTRACT: A novel experiment device was employed to investigate the tensile strength and fracture mechanism of single abaca fibers. Twenty specimens of untreated single fibers with a gauge length of 30 mm were subjected to tensile force with a loading rate of 0.46 N/s. Results show that the tensile strength of the fiber ranges from 417 MPa to 1548 MPa. The tensile strength was calculated using the measured value of cross-sectional area of each fiber, evaluated by using a three-dimensional microscopic observation. The observation conducted for all specimens reveals the fracture mechanism of the single fiber classified into three types, i.e. shear, tension, and combined of shear and tension. The considerably high tensile strength of the single fiber and fracture mechanism of the single fiber provide a possibility for designing high strength abaca fiber reinforced composite for various engineering applications.